Erratum: Convolutidae (Acoela) from Tanzania by Achatz & Hooge (2006) - Achatz, Johannes G.; Hooge, Matthew D. (Zootaxa, 2007)
Due to a failure in the transmission of electronic files, the line drawings in Achatz & Hooge (2006) were printed in an inappropriate layout. They are properly published herein.